THE RELATIONSHIP BETWEEN HEDONIC LIFESTYLE AND STUDENT SELF-CONTROL - Tri Octaviani Qodriah; Rina Nurhudi Ramdhani (Universitas Pendidikan Indonesia, 2024)
This study investigates the relationship between hedonic lifestyle and self-control among university students using both quantitative and qualitative approaches. The quantitative component involved surveying 31 students with standardized scales measuring hedonic lifestyle and self-control. The qualitative aspect included in-depth interviews with some students to gain deeper insights into their behaviours and perceptions. Results from the quantitative analysis revealed a significant inverse correlation between hedonic lifestyle and self-control, indicating that higher engagement in hedonic activities is associated with lower self-control. Qualitative findings supported this, uncovering themes of impulsivity and short-term gratification impacting academic and personal goals. The study concluded that there is a mutually bound relationship between hedonic lifestyle and self-control, where each variable influence and is influenced by the other. These results suggest the need for strategies to help students develop better self-regulation skills while managing a hedonic lifestyle. Further research should explore these dynamics over time to understand causality and long-term effects.